Expression of Heterologous OsDHAR Gene Improves Glutathione (GSH)-Dependent Antioxidant System and Maintenance of Cellular Redox Status in Synechococcus elongatus PCC 7942 - Kim, Young-Saeng; Park, Seong-Im; Kim, Jin-Ju; Boyd, Joseph S.; Beld, Joris; Taton, Arnaud; Lee, Kyoung-In; Kim, Il-Sup; Golden, James W.; Yoon, Ho-Sung (Frontiers in plant science, 2020)
An excess of reactive oxygen species (ROS) can cause severe oxidative damage to cellular components in photosynthetic cells. Antioxidant systems, such as the glutathione (GSH) pools, regulate redox status in cells to guard against such damage. Dehydroascorbate reductase (DHAR, EC 1.8.5.1) catalyzes the glutathione-dependent reduction of oxidized ascorbate (dehydroascorbate) and contains a redox active site and glutathione binding-site. The gene is important in biological and abiotic stress responses involving reduction of the oxidative damage caused by ROS. In this study, transgenic PCC 7942 (TA) was constructed by cloning the L. ( ) gene controlled by an isopropyl β-D-1-thiogalactopyranoside (IPTG)-inducible promoter ( ) into the cyanobacterium to study the functional activities of under oxidative stress caused by hydrogen peroxide exposure. expression increased the growth of PCC 7942 under oxidative stress by reducing the levels of hydroperoxides and malondialdehyde (MDA) and mitigating the loss of chlorophyll. DHAR and glutathione -transferase activity were higher than in the wild-type PCC 7942 (WT). Additionally, overexpression of in PCC 7942 greatly increased the glutathione (GSH)/glutathione disulfide (GSSG) ratio in the presence or absence of hydrogen peroxide. These results strongly suggest that attenuates deleterious oxidative effects via the glutathione (GSH)-dependent antioxidant system in cyanobacterial cells. The expression of heterologous in PCC 7942 protected cells from oxidative damage through a GSH-dependent antioxidant system via GSH-dependent reactions at the redox active site and GSH binding site residues during oxidative stress.